Difference between revisions of "1966 AHSME Problems/Problem 36"
(→Solution) |
(→Solution 2) |
||
Line 8: | Line 8: | ||
== Solution 2 == | == Solution 2 == | ||
+ | |||
+ | Let f(x)=(1+x+x^2)^n then we have | ||
+ | <math>s=a_0+a_1+a_2+...a_{2n}=f(1)=(1+1+1)^n=3^n</math> | ||
== See also == | == See also == |
Revision as of 21:01, 23 December 2019
Contents
Problem
Let be an identity in . If we let , then equals:
Solution
Solution 2
Let f(x)=(1+x+x^2)^n then we have
See also
1966 AHSME (Problems • Answer Key • Resources) | ||
Preceded by Problem 35 |
Followed by Problem 37 | |
1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 • 16 • 17 • 18 • 19 • 20 • 21 • 22 • 23 • 24 • 25 • 26 • 27 • 28 • 29 • 30 | ||
All AHSME Problems and Solutions |
The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions.